Prevalence of sleep disturbance among nurses in a Malaysian government hospital and its association with work characteristics - Nazatul, S.M.; Saimy, I.; Moy, Foong Ming; Nabila, A.S. (Faculty of Medicine, University of Malaya, 2008)
The objective of this study was to determine the prevalence of sleep disturbance with work characteristics among nurses in the Melaka Hospital, Malacca, Malaysia. This was a cross sectional study conducted in Melaka Hospital. Universal sampling was conducted and a Malay version of the Pittsburgh Sleep Quality Index (PSQI) questionnaire was used in data collection. Sociodemographic characteristics such as age, marital status, number of children and work characteristics such as type of work schedule and duration were also enquired. Factors associated with poor sleep quality were compared between those nurses with good sleep quality by using logistic regression. There were 607 nurses who completed the questionnaire with a response rate of 73.1. There was a moderate prevalence (57.8) of poor sleep quality (PSQI > 5) in all study subjects. The prevalence of sleep disturbance was more widespread among nurses who worked shifts (62.0) compared to non-shift working nurses (41.5) p<0.001. A logistic regression analysis showed that age, marital status and unit group were the major associating factors of poor sleep quality. Sleep disturbance decreased with increasing age (OR = 0.42, 95 CI 0.25, 0.73) while married nurses (OR = 2.3, 95 CI 1.42, 3.82) and those in the category of intensive group (OR = 2.1, 95 CI 1.1, 4.1) were more prone to have sleep disturbances. In conclusion, this study revealed moderate prevalence of sleep disturbance among nurses working in Melaka Hospital but it was not associated with the work shifts. Age, marital status and work environment especially in the intensive group unit seemed to be factors associated with reduced global sleep quality among nurses in this study. (JUMMEC 2008; 11 (2): 66-71).